To solve the equation 8x - 2(x + 1) = 2(3x - 1), we will proceed as follows:
8x - 2x - 2 = 6x - 2
Combining like terms, we have:
6x - 2 = 6x - 2
Since the variables and constants on both sides of the equation are the same, we can say that this equation has infinitely many solutions. Therefore, the correct response is "no solution."
8x – 2(x + 1) = 2(3x – 1)
(1 point)
Responses
0
0
2
2
no solution
5 answers
3(c – 2) = 2(c – 6)
(1 point)
Responses
2
2
−6
−6
no solution
no solution
identity
(1 point)
Responses
2
2
−6
−6
no solution
no solution
identity
To solve the equation 3(c - 2) = 2(c - 6), we will distribute and simplify:
3c - 6 = 2c - 12
Next, we will isolate the variable c by moving all terms with c to one side of the equation:
3c - 2c = -12 + 6
c = -6
The value of c that satisfies the equation is -6. Therefore, the correct response is "-6".
3c - 6 = 2c - 12
Next, we will isolate the variable c by moving all terms with c to one side of the equation:
3c - 2c = -12 + 6
c = -6
The value of c that satisfies the equation is -6. Therefore, the correct response is "-6".
0.5(m + 4) = 3(m – 1)
(1 point)
Responses
–2
–2
2
2
no solution
no solution
identity
(1 point)
Responses
–2
–2
2
2
no solution
no solution
identity
To solve the equation 0.5(m + 4) = 3(m - 1), we will distribute and simplify:
0.5m + 2 = 3m - 3
Next, we will isolate the variable m by moving all terms with m to one side of the equation:
0.5m - 3m = -3 - 2
-2.5m = -5
Dividing both sides of the equation by -2.5:
m = 2
The value of m that satisfies the equation is 2. Therefore, the correct response is "2".
0.5m + 2 = 3m - 3
Next, we will isolate the variable m by moving all terms with m to one side of the equation:
0.5m - 3m = -3 - 2
-2.5m = -5
Dividing both sides of the equation by -2.5:
m = 2
The value of m that satisfies the equation is 2. Therefore, the correct response is "2".